ANALISIS IMPLEMENTASI KURIKULUM MERDEKA PADA PELAJARAN AL-QUR’AN HADITS DI MTS N 3 SLEMAN - Amalia Afizah; Muh. Wasith Achadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The Merdeka curriculum is a curriculum that gives more autonomy to schools and teachers in designing and implementing the curriculum. The purpose of this study is to analyze the implementation of the Merdeka curriculum in the Al-Qur'an Hadith subject at MTs N 3 SLEMAN. The research method used is field research with a qualitative descriptive approach. Data collection techniques using observation, interviews and documentation. Data analysis techniques with data collection, data reduction, data presentation and then drawing conclusions. The results of this study indicate that in the process of implementing the Merdeka curriculum, it faces several obstacles, such as the lack of facilities, the lack of educators in the Al-Qur'an Hadith subject, the teacher readiness factor and not all books labeled as Merdeka learning materials are in accordance with the Merdeka curriculum. However, with various problems, educators in madrasas always provide their best efforts for the effective running of the learning process with the Merdeka curriculum.